The Influence Of Occupational Health and Safety, Physical Work Environment and Work Motivation On Job Satisfaction - Epsilandri Septyarini; Taufiqurrohman Noor Ridho; Prayekti Prayekti (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2023)
The research objective was to determine the effect of Occupational Health and Safety, Physical Work Environment, and Motivation on Worker Satisfaction. This type of research is quantitative research with descriptive analysis to assess a data characteristic. The population in this research object is 70 people, and the sample of all members of the population is 70 people. Saturated sample is a sampling technique in this study, because it uses all members of the existing population. The data collection method used a questionnaire and was analyzed using the method of multiple linear regression analysis with SPSS version 22. The results showed that Occupational Health and Safety had a positive and significant effect on Worker Satisfaction, the Physical Work Environment did not have a positive and significant effect on Worker Satisfaction, Motivation had an effect positive and significant to Employee Satisfaction. As well as Occupational Health and Safety, Physical Work Environment, and Motivation simultaneously affect Worker Satisfaction